Evaluating Public Perception and Awareness of Internet Fraud among Residents in Nigeria - Bemgba, Paul Terlumun (African Journal of Stability and Development (AJSD), 2025)
As Nigeria deepens its engagement with the digital economy, internet fraud has emerged as a pervasive and socially complex challenge. What began in the 1990s with rudimentary email scams known as “419 fraud” has evolved into highly sophisticated schemes involving phishing, identity theft, cryptocurrency fraud, and Business Email Compromise (BEC). Despite extensive interventions by state agencies such as the Economic and Financial Crimes Commission (EFCC), the Nigeria Police Force Cybercrime Unit, and collaborations with international bodies like INTERPOL and the FBI, internet fraud continues to thrive, particularly among Nigerian youths. This study evaluates public perception and awareness of internet fraud within Nigeria, focusing on how socio-economic hardship, youth unemployment, cultural narratives, and media portrayals shape societal attitudes towards cybercrime. Using a mixed-method approach anchored in survey data and qualitative content analysis, the study explores the paradox of widespread condemnation of cybercrime alongside pockets of social acceptance and even glorification, especially among disenfranchised youths. Prominent cases, such as the arrests of Ramon Abbas (Hushpuppi), Obinwanne Okeke (Invictus Obi), and the rise of “Yahoo Academies,” underscore the extent to which cybercrime is embedded in socio-cultural and economic systems. Public figures convicted of internet fraud are often simultaneously vilified and idolised, reflecting complex perceptions of success, justice, and opportunity in a society plagued by poverty and systemic corruption. Findings such as a 2019 NOIPolls survey indicating that 32% of youths knew someone involved in cybercrime further reveal normalisation tendencies among vulnerable demographics. The research identified several critical drivers behind the public perception of internet fraud, including structural unemployment, poor digital literacy, ineffective law enforcement, peer pressure, and media glamourisation. Furthermore, it highlighted key demographic variations in public opinion, based on age, education, gender, and region. The paper argues that existing legal and punitive responses must be supplemented by culturally informed public education, youth empowerment initiatives, ethical media regulation, and rehabilitative strategies. Only through a holistic understanding of the socio-economic and psychological dimensions of internet fraud can Nigeria develop effective policies that shift public perception and fortify digital integrity in its emerging economy.